Algunos aspectos teóricos de las funciones casi periódicas n-dimensionales - Arguedas, Vernor (2000)
We five a definition of Almost Periodic Functions on RN. Following that definition we show some topological properties for this functions. At the end of this paper we proof some algebraic properties by using the structure theorem. We give the proof of this result (structure theorem) in the appendix.